The Effect of Chia Seeds (Salvia hispanica L.) Addition on Quality and Nutritional Value of Wheat Bread - Daria Romankiewicz; Waleed Hameed Hassoon; Grażyna Cacak-Pietrzak; Małgorzata Sobczyk; Magdalena Wirkowska-Wojdyła; Alicja Ceglińska; Dariusz Dziki (Journal of Food Quality)
The aim of the study was to analyze and characterize the influence of chia seeds (CS) addition (0, 2, 4, 6, and 8%) on wheat bread properties. Bread properties that underwent evaluation included chemical composition, fatty acid composition, total phenolics content, volume, baking losses, crumb texture, and color and sensory analysis. The addition of CS decreased baking losses and the volume of bread. The color of the crumb with CS was much darker as compared with the control sample. The texture analysis showed that the CS caused a decrease in the hardness of the crumb. Most importantly, the addition of CS increased the nutritional value of the bread. Bread with CS contained more dietary fiber and mineral components. Moreover, it has been observed that in comparison to the control product bread with CS was characterized by a rich fatty acids composition and higher level of phenolic compounds. Most importantly, the results showed that the substitution of wheat flour with chia seeds up to 6% did not negatively affect the final product acceptance.